IL-17A- versus IL-17F-induced intracellular signal transduction pathways and modulation by IL-17RA and IL-17RC RNA interference in rheumatoid synoviocytes. Issue 2 (24th November 2010) - Hot, Arnaud; Zrioual, Saloua; Toh, Myew-Ling; Lenief, Vanina; Miossec, Pierre
Abstract : Objective: The aim of this study was to compare the effects of interleukin (IL)-17A and IL-17F on gene expression and signalling in human rheumatoid arthritis (RA) synoviocytes. Methods: IL-17A- and IL-17F-induced mRNA expression was analysed using Affymetrix microarrays. IL-6 and IL-8 secretion was evaluated by ELISA. Inhibition of two receptors (IL-17RA and IL-17RC) was achieved by small interfering RNA (saran). The effects on mitogen-activated protein kinase (MAPK), activator protein 1 (AP-1) and nuclear factor κB (NF-κB) expression and activation were evaluated by western blotting, qRT-PCR and DNA binding assay. Results: IL-17A and IL-17F induced a molecular pattern characterised by 27 inflammation-related genes for IL-17F and 165 for IL-17A. Virtually all IL-17A and IL-17F inducible genes were dependent on NF-κB activation, whereas a small number were modulated by p38. IL-17A induced activation of all three MAPKs (ERK, p38 and JNK) and downstream transcription factors AP-1 and p65 NF-κB. IL-17F was less potent but induced activation of p50 NF-κB. IL-17A was more potent at inducing IL-6 secretion than IL-17F, which was inactive alone. IL-17A and, to a lesser extent, IL-17F induced TRAF6 but not MyD88. Inhibition of either IL-17RA or IL-17RC expression via siRNA led to near complete abrogation of IL-6 expression mediated by IL-17A and the combination of IL-17F and tumour necrosis factor α. Conclusion: Like IL-17A, IL-17F regulates proinflammatory gene expression by a very similar but not identical signalling pathway involving IL-17RA and IL-17RC.